Complete Genome of Lactobacillus iners KY Using Flongle Provides Insight Into the Genetic Background of Optimal Adaption to Vaginal Econiche - Kwak, Woori; Han, Young-Hyun; Seol, Donghyeok; Kim, Hyaekang; Ahn, Hyeonju; Jeong, Misun; Kang, Jaeku; Kim, Heebal; Kim, Tae Hyun (Frontiers in Microbiology, 2020)
Despite the importance of Lactobacillus iners and its unique characteristics for the study of vaginal adaption, its genome and genomic researches for identifying molecular backgrounds of these specific phenotypes are still limited. In this study, the first complete genome of L. iners was constructed using a cost-effective long-read sequencing platform, Flongle from Oxford Nanopore, and comparative genome analysis was conducted using a total of 1,046 strain genomes from 10 vaginal Lactobacillus species. Single-molecule sequencing using Flongle effectively resolved the limitation of the 2nd generation sequencing technologies in dealing with genomic regions of high GC contents, and comparative genome analysis identified three potential core genes (INY, ZnuA, and hsdR) of L. iners which was related to its specific adaption to the vaginal environment. In addition, we performed comparative prophage analysis for 1,046 strain genomes to further identify the species specificity. The number of prophages in L. iners genomes was significantly smaller than other vaginal Lactobacillus species, and one of the specific genes (hsdR) was suggested as the means for defense against bacteriophage. The first complete genome of L. iners and the three specific genes identified in this study will provide useful resources to further expand our knowledge of L. iners and its specific adaption to the vaginal econiche.